A hydrological comparison between two watersheds in Pohangina County : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Agricultural Science at Massey University - Rolston, Shirley Jean (Massey University, 1973)
The study area consists of two adjacent catchments situated on the unconsolidated Castlecliffian Sand country in the Pohangina County. This parent material was first recognized as an erosion problem with respect to canyon gullying in the middle 1930s, and since the late 1940s has been an area of major concern for the Manawatu Catchment Board. Various conservation structures and extensive planting of different exotic tree species, coupled with improved pasture and stock management, have resulted in the near stabilization of some of the watersheds in the district. Other watersheds are still contributing unknown quantities of sediment to the Oroua and Pohangina Rivers in each runoff event. This study, although mainly qualitative in approach, endeavours to compare the sediment loads produced at peak runoff times in 1972 by the two study catchments. Flood level recorders were installed to provide an indication of the peak levels reached by flood waters. With the simple equipment available, flood water samples were taken as near to the flood peak as could be judged. Mechanical analyses carried out on these samples determined the proportions of coarse sand, fine sand, silt and clay in the sediment load.
Keywords: Pohangina; Soil erosion; Watershed stabilisation; Pohangina river; Sediments